Synergising youth empowerment and co-design to transform Pasifika youth into agents of social change : a novel approach to advance healthy lifestyles in Pasifika communities : a thesis presented in partial fulfilment of the requirements of Doctor of Philosophy in Public Health at Massey University, Wellington campus, New Zealand - Prapavessis, Dani (Massey University, 2020)
Current population health statistics demonstrate the need for innovative approaches to improve health outcomes and prevent non-communicable disease (NCD) for Pasifika peoples. This research builds off pilot studies on the effects of youth empowerment programmes to address obesity-related issues amongst Pasifika communities. It developed and tested an original model of co-design embedded within the youth empowerment framework of the Pasifika Prediabetes Youth Empowerment Programme. The programme was co-delivered with two community health service providers (one rural and one urban), employing Community-Based Participatory Research (CBPR) methodology. N=29 youth (aged 15-24 years) participated in eleven educational and capacity-building modules that comprised the empowerment and co-design components during weekly sessions from May-October 2018. At the end of the programme, the model of co-design generated two individualised community intervention action plans to reduce prediabetes in their communities. This research employed a qualitative research design with four data collection techniques and thematic analysis to evaluate the effects of the tested programme. It used an original framework of social change to determine the impacts on the youth’s values, knowledge, and behaviours as well as the community organisations, and the socio-cultural norms of each community. It also explicated the contextual considerations of programme uptake in each location. Overall, this research illustrated that co-design is an effective addition to empowerment frameworks. It demonstrated how to operationalise co-design in a community-based setting with youth, and the tested model provided a practical framework to translate empowerment ii outcomes into the community. The programme analyses also led to a more nuanced understanding of social change. This research developed a concept of the process of social change that can be used to inform future programme development and evaluation. This research suggests future translations of the programme to maximise uptake and postulates different community contexts and settings for delivery, beyond Pasifika prediabetes prevention.
Keywords: Pacific Islanders; Youth; Health and hygiene; New Zealand; Health promotion; Social change; 451607 Pacific Peoples health promotion; 451619 Pacific Peoples theory of change models for health